Formation of a sustainable mechanism of preferential VAT taxation of exports as evidenced by the Russian Federation practice - Elena Sidorova; Ekaterina Sebechenko; Yury Kostyukhin; Diana Boboshko; Alexey Kostin; Olga Kostina; Natalia Vikhrova (Economies, 2021)
In this article we review the issues of applying a preferential value added tax (VAT) taxation regime on export transactions involving unlawful tax benefit claims and tax evasion. The main objective of this study is to supplement the theoretical and methodological foundations of transforming the system of indirect taxation of exports in the Russian Federation based on the analysis of legal precedents. We analyzed the foreign trade statistics for the Russian Federation and the volumes of export VAT; we also studied the court rulings in VAT-related tax disputes. Based on our analysis of the court cases, we discovered the main schemes of unlawful application of VAT preferences, such as "false exports", introduction of additional layers of intermediaries, and use of agency services by exporting sellers. In addition, we formulated two problematic scenarios where bona fide transactions fall under the definition of such schemes. Specifically, these two scenarios include services contracts by foreign service providers that are reclassified by the tax authorities with an aim to challenge the offsetting of incoming VAT amounts and the specifics of applying VAT to transactions involving compensation-free transfer of goods to foreign legal entities. To minimize the number of tax disputes, we suggest that certain provisions of the Russian legislation are amended with more detail. The proposed innovations can positively affect international trade as they bring more easily understandable and stable conditions for the development of businesses engaged in cross-border service provisioning. At the same time, a reduction in the number of disputes based on the tax authorities' subjective opinion of taxpayers' activities would allow the tax authorities to concentrate on clearer and more objective criteria of tax compliance by Russian companies, thus simplifying tax administration in one of the domains of tax law.
Keywords: 330; emerging economies sustainable development goals; export operations; preferential taxation; VAT